The use of ultrasonic echo pulse velocity as an NDT method to predict the concrete strength and uniformity - Abreu Filho, Marco Antonio (2022)
The ultrasonic approach is one of the non-destructive testing methods that most technologically progressed in past few years. This study aims to validate the accuracy and capabilities of this method in the mechanical characterization of concrete elements, by using an ultrasonic tomography equipment based in echo pulse velocity (S-waves). The elastic modulus and compressive strength of concrete are estimated from the echo pulse velocity. Furthermore, the uniformity of concrete elements is evaluated. The concrete compression strength prediction was performed on cubic specimens and the reached accuracy was over 91% using the analytical approach proposed on this study. The correlation coefficient between the pulse echo velocity and the uniaxial compression strength found in this study was over 97%. Thus, the use of the ultrasonic NDT to evaluate the uniformity of concrete elements proved to be efficient.